Český botanický výzkum na Svalbardu - Klimešová, Jitka , 1963-; Prach, Karel , 1953-
Czech botanists have studied the vegetation of Northern Biljefjorden (Central Spitsbergen) since 2007. Their activities include vegetation mapping of the whole area (repeated also after 70 years), assessment of vegetation development in deglaciated areas and analysis of clonal growth forms. Jitka Klimešová, Karel Prach.